So I learned that you can use the product rule to guess what the derivative of $\frac{1}{x}$ should be, you just use the fact that $(\frac{1}{x}\cdot x) = 1$ and differentiate both sides and solve for $(\frac{1}{x})'$. My teacher said that there is a similar trick for guessing the derivative of $(\frac{1}{x})$ using the chain rule, I tried using the fact that $\frac{1}{x}\circ\frac{1}{x}= x$ but I am stuck.

  • 2
    $\begingroup$ You won’t be able to get it from the fact that $f\circ f= \mathrm{id}$ (what you are trying to do), because $f(x) = \frac{1}{x}$ is not the only function with this property: if you have $g(x) = -x$, then you also have that $g\circ g = \mathrm{id}$, but of course $f’(x)\neq g’(x)$. In short, you are barking up the wrong tree trying to use that property. $\endgroup$ – Arturo Magidin Feb 3 '19 at 23:15
  • $\begingroup$ @ArturoMagidin I think that claim is premature just from your comments. It's the wrong tree if one is going for $f\circ f$, but there could be some other useful compositions. $\endgroup$ – Git Gud Feb 3 '19 at 23:17
  • $\begingroup$ @GitGud: I very carefully did not say anything about using the chain rule in general. I very specifically and explicitly talked about the specific attempt at using the fact that $f\circ f = \mathrm{id}$, which is in fact what the OP is talking about. So, since my comment is only about “going for $f\circ f$,” explicitly (which I specify twice), I have to say your comment is addressing a strawman in which I have no part. $\endgroup$ – Arturo Magidin Feb 3 '19 at 23:20
  • $\begingroup$ @ArturoMagidin I was about to add an adendum to my comment saying that my comment assumed that "property" meant the composition. I stand corrected. $\endgroup$ – Git Gud Feb 3 '19 at 23:22
  • $\begingroup$ Using $x=1/(\frac1x)=u(v(x))$ just leads to $\frac{dv}{du}=\frac{dv}{dx}$, which is obviously true since $u(x) =x. $ So this is the wrong composition to try. $\endgroup$ – timtfj Feb 4 '19 at 1:17

$$f(x)=\frac1x$$ $$\log \circ \,\,f=-\log x$$ $$(\log \circ \,\,f)’=(-\log x)’$$ $$f’\frac 1f=-\frac1x$$ $$f’=-\frac fx=-\frac 1{x^2}$$


This works, but I'm not sure if it is allowed. Depends on whether you know the derivative of $\log$.

For any positive real number $x$, set $f(x)=\dfrac 1 x, g(x)=\log(x)$ and $h(x)=-\log(x)$. Note that $g\circ f=h$ and

$$ \begin{align} (g\circ f)(x) = h(x) &\implies g'(f(x))f'(x)=h'(x)\\ &\implies f'(x) = h'(x)/g'(f(x))\\ &\implies f'(x)=-\log'(x)/\log'\left(1/x\right)\\ &\implies f'(x) = -\dfrac{\frac{1}{x}}{\frac{1}{1/x}}\\ &\implies f'(x) = -\dfrac{1}{x^2} \end{align} $$

The crucial point here is that $g'=f^{-1}$. Not unlike what I did here.

  • 1
    $\begingroup$ At least you've answered the actual question! $\endgroup$ – timtfj Feb 4 '19 at 1:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.